2000
DOI: 10.1089/end.2000.14.735
|View full text |Cite
|
Sign up to set email alerts
|

Nephrostomy Tube after Percutaneous Nephrolithotomy: Large-Bore or Pigtail Catheter?

Abstract: A pigtail catheter nephrostomy tube after PCNL reduces the hospital stay by reducing the duration of the urinary leak. The postoperative course is smooth, as patient has less pain and needs less analgesic support. There is no statistically significant increase in the postoperative bleeding secondary to use of a pigtail catheter. Second-look nephroscopy was easy in the one patient with a pigtail nephrostomy catheter who needed the procedure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
38
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(39 citation statements)
references
References 6 publications
1
38
0
Order By: Relevance
“…[18,19] In contrast, in a prospective study, Maheshwari and coworkers demonstrated no significant increase in the postoperative bleeding in 20 patients who underwent a one-stage tubeless PCNL. [20] In the present study, 3 of 120 cases (2.5%) developed perinephric collection ranging from 50-100 cc. These cases were managed conservatively, and the collections resolved spontaneously within one week.…”
Section: Discussionsupporting
confidence: 42%
“…[18,19] In contrast, in a prospective study, Maheshwari and coworkers demonstrated no significant increase in the postoperative bleeding in 20 patients who underwent a one-stage tubeless PCNL. [20] In the present study, 3 of 120 cases (2.5%) developed perinephric collection ranging from 50-100 cc. These cases were managed conservatively, and the collections resolved spontaneously within one week.…”
Section: Discussionsupporting
confidence: 42%
“…In our patients we didn't see any child needing renal arterial embolisation or nephrectomy for postoperative bleeding. Maheshwari et al [22] performed a prospective study on 40 patients who had undergone either 28 F nephrostomy tube or 9 Fr pigtail catheter insertions at the end of the PCNLs. They reported relatively shorter duration of the urinary leakage and hospital stay, with reduced pain and lesser need for analgesia in pigtail nephrostomy group.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, a nephrostomy tube was associated with patients' discomfort and prolonged hospital stay. These were the main reasons to use a small nephrostomy tube or to omit the placement of it in the so called ''tubeless'' PCNL [6,7]. We think that the term ''tubeless'' is misleading because in many series the kidney was drained with either internalized or externalized ureteral stents [7,17].…”
Section: Discussionmentioning
confidence: 99%
“…However, the nephrostomy tube was associated with patients' discomfort and prolonged hospital stay. Therefore, the large sized tube of 16-22 French (F) was replaced with smaller tubes (8-9 F) [5,6].…”
Section: Introductionmentioning
confidence: 99%